High-wear-resistance molybdenum disulfide / fluorinated graphene composite material lubricating additive and preparation method thereof

The lubricating additive of molybdenum disulfide/fluorinated graphene composite material is prepared by ionic liquid-assisted in situ peeling method and hydrothermal reaction method, which solves the problems of complex preparation process and the use of toxic solvents in the prior art, and achieves stable dispersion of composite materials and excellent lubricating properties.

CN119391468AActive Publication Date: 2025-02-07SHAANXI UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411440387.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-07
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

In the prior art, when improving friction and wear performance, the preparation process is complicated and the use of toxic solvents is lacking in green environmental protection and sustainability, and molybdenum disulfide and graphene fluorinated are difficult to disperse uniformly in the medium.

Method used

Molybdenum disulfide is peeled in water by ionic liquid-assisted in situ peeling method, and the fluorinated graphene is peeled in combination with hydrothermal reaction method to form a lubricating additive for molybdenum disulfide/fluorinated graphene composite material. Through ultrasonic dispersion and mechanical crushing treatment, each is ensured. Excellent dispersion and stability of components.

Benefits of technology

It realizes the stable dispersion and excellent lubricating properties of the composite material, reduces friction and wear, and has a simple preparation process, no pollution, low cost, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391468A_ABST
    Figure CN119391468A_ABST
Patent Text Reader

Abstract

The invention discloses a high-wear-resistance molybdenum disulfide / fluorinated graphene composite material lubricating additive and a preparation method thereof. The preparation method comprises the following steps: dispersing an ionic liquid in distilled water, and then adding molybdenum disulfide to form a mixed solution; sequentially carrying out ultrasonic treatment, multiple mechanical crushing treatment and centrifugal treatment, and then taking supernate to obtain molybdenum disulfide dispersion liquid; the preparation method comprises the following steps: dispersing an ionic liquid in distilled water, then adding graphite fluoride to form a mixed solution, then putting the mixed solution into a high-pressure kettle for hydrothermal reaction, and then taking supernate after centrifugal treatment to obtain a fluorinated graphene dispersion liquid; and mixing the molybdenum disulfide dispersion liquid and the fluorinated graphene dispersion liquid according to the mass ratio of (1-3): 1, and performing ultrasonic treatment to form the molybdenum disulfide / fluorinated graphene composite material lubricating additive. The synthesis method is simple, wide in raw material source, low in cost, free of pollution and more suitable for industrial popularization and application. The prepared material has excellent stability and high wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, relates to composite materials and a preparation method thereof, and specifically relates to a highly wear-resistant molybdenum disulfide / fluorinated graphene composite material lubricating additive and a preparation method thereof. Background Art

[0002] Friction and wear are everywhere in our lives. Friction consumes about one-third of the world's primary energy, while wear causes about 60% of machine parts to fail. In addition, more than 50% of mechanical equipment accidents are caused by lubrication failure and excessive wear. These factors not only cause the loss of surface materials, but also directly affect the service life of parts, resulting in serious waste of resources and energy.

[0003] Two-dimensional materials have attracted much attention due to their thin layer structure and large specific surface area. The weak interlayer interaction between adjacent atomic layers allows these materials to significantly improve the performance of lubricants when used as additives. They form a protective layer by sliding on the metal surface, effectively reducing friction and wear. When multiple nanomaterials are combined, the synergistic effect can not only achieve superlubricity, but also improve the corrosion resistance and mechanical properties of the contact interface.

[0004] Among many two-dimensional materials, molybdenum disulfide (MoS) is one of the most representative materials among transition metal sulfides. A single layer of MoS has three atomic planes. The middle Mo atomic plane separates the S atoms of the two hexagonal edge planes. The layers are bonded by strong covalent bonds or ionic bonds. Adjacent layers are bonded by weak van der Waals forces. Therefore, external forces can be easily used to break the interlayer constraints to form a thinner few-layer MoS. At the same time, it is very easy to slip and show a good friction reduction effect, which makes MoS have a lower friction coefficient. However, due to its high specific surface area, MoS has a strong tendency to agglomerate between particles. This agglomeration phenomenon will cause the particles to form large agglomerates, making it difficult to achieve uniform dispersion in the medium.

[0005] Fluorinated graphene (FG) also has excellent lubrication properties. As a component unit of [CFX]n, FG inherits the advantages of graphene, has a wide interlayer spacing and weak interlayer force, can reduce the friction resistance between materials, and can act as an additive in liquid lubricating materials. At the same time, the high thermal conductivity of fluorinated graphene can dissipate the friction heat generated during sliding motion. However, the friction coefficient of single fluorinated graphene is not low enough on a macroscopic scale, and its lubrication performance is largely restricted by the external environment. Therefore, fluorinated graphene is compounded with other lubricating materials to solve the problems in the friction and wear process through the synergistic effect between different materials to achieve better tribological properties. Molybdenum disulfide and fluorinated graphene are similar two-dimensional layered nanomaterials. Through compounding to form a new heterogeneous structure, there is interaction to achieve synergistic lubrication and obtain more excellent performance.

[0006] The invention patent of application number CN118048199A discloses a lubricating additive and application of a molybdenum disulfide / modified nitrogen-doped graphene composite material. Molybdenum disulfide is modified with a silane coupling agent with an epoxy group, and graphene oxide is modified with a silane coupling agent with an amino group. The modified graphene oxide is then ball-milled with ammonium bicarbonate to obtain modified nitrogen-doped graphene. The modified molybdenum disulfide and the modified nitrogen-doped graphene are then grafted to obtain a lubricating additive of a molybdenum disulfide / modified nitrogen-doped graphene composite material that can be used as solid-liquid lubrication. Although the above invention effectively improves wear resistance, it is easy to cause agglomeration of graphene oxide during the preparation process, and the preparation process is complicated. The invention patent of application number CN109233177A discloses a molybdenum disulfide / fluorinated graphene-polytetrafluoroethylene composite material and its preparation method and application, which comprises polyvinyl pyrrolidone, polytetrafluoroethylene grafted with 4-aminostyrene, and fluorinated graphene loaded with molybdenum disulfide. Although the above invention effectively improves the wear resistance, toxic solvents are used in the preparation process, which is not environmentally friendly and sustainable, and the preparation process is complicated. Summary of the invention

[0007] The present invention aims to provide a highly wear-resistant molybdenum disulfide / fluorinated graphene composite material lubricating additive and a preparation method thereof. The preparation process of the present invention is simple, pollution-free and low-cost, and the prepared composite material has stable dispersibility and excellent lubrication performance.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] A highly wear-resistant molybdenum disulfide / fluorinated graphene composite material lubricating additive and a preparation method thereof, comprising the following steps:

[0010] Step 1: Weigh 250-350 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water to form an ionic liquid aqueous solution, add 500 mg of molybdenum disulfide, and then perform ultrasonic dispersion, multiple mechanical crushing treatments and centrifugation treatments to obtain the supernatant to obtain a molybdenum disulfide dispersion;

[0011] Step 2: Weigh 350-450 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water, add 200 mg of graphite fluoride and perform ultrasonic dispersion, then put it into an autoclave for hydrothermal reaction to obtain an initial fluorinated graphene suspension, and take the supernatant after centrifugation to obtain a fluorinated graphene dispersion;

[0012] Step 3: Mix the molybdenum disulfide dispersion and the fluorinated graphene dispersion in a mass ratio of (1-3):1, and perform ultrasonic treatment to form a molybdenum disulfide / fluorinated graphene composite lubricating additive.

[0013] Furthermore, the ultrasonic dispersion time in step 1 is 25 to 30 minutes.

[0014] Furthermore, the total time of the multiple mechanical crushing treatments in step 1 is 30 to 40 minutes, each mechanical peeling lasts for 10 minutes, and the interval between each mechanical peeling is 5 to 10 minutes.

[0015] Furthermore, the rotation speed of the centrifugal treatment in step 1 is 2500-3000 rpm, and the centrifugation time is 20-30 min.

[0016] Furthermore, the hydrothermal reaction time in step 2 is 18 to 24 hours, and the hydrothermal reaction temperature is 150 to 200°C.

[0017] Furthermore, the rotation speed of the centrifugal treatment in step 2 is 3000-3500 rpm, and the centrifugation time is 20-30 min.

[0018] Furthermore, the ultrasonic treatment time in step 3 is 30 to 40 minutes.

[0019] The structure of the molybdenum disulfide / fluorinated graphene composite lubricating additive prepared by the above preparation method is that molybdenum disulfide nanosheets with a lateral size of 100-300 nm are loaded on fluorinated graphene nanosheets with a lateral size of 1.03 μm.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The preparation method of the present invention is simple, does not require unnecessary impurity removal steps, and the solvent used in the whole process is green, environmentally friendly and pollution-free. And there are excellent dispersibility, stability and lubricity between the components, the implementation process is easy to control, the preparation cost is low, and it is suitable for industrial production. Only need to simply adopt ionic liquid assisted in-situ stripping method to strip molybdenum disulfide MoS2 in water, use amphiphilic ionic liquid ILs as green stripping agent, not only help to strip bulk MoS2 into ultra-thin MoS2 nanosheets, ultra-thin MoS2 nanosheets Π-Π interaction is limited by ionic liquid ILs, avoid direct contact of MoS2 nanosheets with water, prevent ultra-thin MoS2 nanosheets from agglomerating in water. Adopt ionic liquid assisted hydrothermal stripping method to strip fluorinated graphene FG from bulk fluorinated graphite, due to the reliable interaction between fluorinated graphene FG and ionic liquid ILs, non-covalently functionalized fluorinated graphene FG nanosheets show good dispersibility in water and organic solvents.

[0022] The molybdenum disulfide / fluorinated graphene composite material lubricating additive prepared by the present invention shows excellent stable dispersibility, excellent self-lubricating performance and high wear resistance. The few-layer molybdenum disulfide nanosheets make the composite material have excellent self-lubricating performance; the CF bond in the fluorinated graphene can make the FG layer slip more easily, which can reduce the friction resistance between the materials and improve the lubricating performance of the composite material. The molybdenum disulfide nanosheets are uniformly loaded on the fluorinated graphene nanosheets, which effectively ensures the dispersibility of molybdenum disulfide on the surface of the fluorinated graphene and inhibits the agglomeration tendency of the molybdenum disulfide nanosheets. At the same time, a chemical bond is formed between the F atoms on the surface of the fluorinated graphene and the S atoms of the molybdenum disulfide. This chemical bond can enhance the mutual attraction between the two and promote their uniform dispersion, which helps to achieve better friction performance and reduce local wear and friction. The fluorinated graphene has excellent thermal conductivity, which can transfer the heat in the friction process in time and reduce the generation of friction heat. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD patterns of molybdenum disulfide, fluorinated graphene and composite materials peeled off in Example 1;

[0024] Figure 2 Raman images of the molybdenum disulfide, fluorinated graphene and composite material peeled off in Example 1;

[0025] Figure 3 Zeta potential diagram of the molybdenum disulfide / fluorinated graphene composite lubricating additive prepared in Example 1 after being placed for different time periods;

[0026] Figure 4 The friction coefficient curve of the molybdenum disulfide / fluorinated graphene composite lubricating additive prepared in Examples 1-3 in a pure water friction environment;

[0027] Figure 5 The friction coefficient curve of the molybdenum disulfide / fluorinated graphene composite lubricating additive prepared in Examples 1-3 in an oil friction environment;

[0028] Figure 6 This is a friction coefficient curve of the molybdenum disulfide / fluorinated graphene composite lubricating additive prepared in Examples 1-3 in an artificial seawater friction environment. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] Example 1: A method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite lubricating additive is as follows:

[0031] Step 1: Weigh 250 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water to form an ionic liquid aqueous solution, add 500 mg of molybdenum disulfide, and then perform ultrasonic dispersion for 30 minutes, and then perform multiple mechanical crushing treatments with a total time of 30 minutes, each mechanical peeling lasts for 10 minutes, and each mechanical peeling is separated by 5 minutes, and finally centrifuged at a speed of 3000 rpm for 20 minutes to remove unpeeled molybdenum disulfide nanosheets, and take the supernatant through a pipette to obtain a molybdenum disulfide dispersion;

[0032] Step 2: Weigh 350 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water, add 200 mg of graphite fluoride and perform ultrasonic dispersion for 30 minutes, then put it into an autoclave for hydrothermal reaction at 150° C. for 24 hours to obtain an initial fluorinated graphene suspension, and finally centrifuge it at 3000 rpm for 30 minutes to remove the unexfoliated fluorinated graphite ([CFX]n) sheets, and take the supernatant by pipette to obtain a fluorinated graphene dispersion;

[0033] Step 3: Mix the molybdenum disulfide dispersion and the fluorinated graphene dispersion in a mass ratio of 1:1, and perform ultrasonic treatment for 30 minutes to form a molybdenum disulfide / fluorinated graphene composite lubricating additive.

[0034] X-ray diffraction (XRD) analysis was performed on the molybdenum disulfide, fluorinated graphene and composite materials peeled off in Example 1 to observe the crystal information and elemental composition of the samples. Figure 1As shown, the diffraction peaks at the positions of 14.3° and 56.8° correspond to the (002)(110) crystal plane of MoS2. The diffraction peaks at the positions of 14.1° and 41° correspond to the (001)(100) crystal plane of fluorinated graphene. It can be seen that the characteristic diffraction peaks of MoS2 and fluorinated graphene both appear in the XRD spectrum of MoS2 / fluorinated graphene nanocomposite materials, indicating that the composite is composed of two substances, MoS2 and fluorinated graphene.

[0035] Raman spectroscopy analysis was performed on the molybdenum disulfide, fluorinated graphene and their composite materials peeled off in Example 1. Figure 2 As shown, the Raman spectrum of the composite material can be observed at 373 cm -1 and 406cm -1 The characteristic peaks that appear correspond to the A1g and E2g characteristic peaks of molybdenum disulfide. -1 and 1590cm -1 The characteristic peaks correspond to the D peak and G peak of F fluorinated graphene. It can be seen that the characteristic peaks of MoS2 and fluorinated graphene both appear in the Raman spectrum of MoS2 / fluorinated graphene nanocomposite materials, indicating that the composite is composed of two substances: MoS2 and fluorinated graphene.

[0036] The composite material prepared in Example 1 was placed for different time periods to observe the change in its Zeta potential. Figure 3 As shown, it can be seen that the absolute value of the Zeta potential of the static dispersion exceeds 25 mV, indicating that the composite material has good dispersion stability.

[0037] Example 2: A method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite lubricating additive is as follows:

[0038] Step 1: Weigh 300 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water to form an ionic liquid aqueous solution, add 500 mg of molybdenum disulfide, and then perform ultrasonic dispersion for 25 minutes, and then perform multiple mechanical crushing treatments for a total time of 40 minutes, each mechanical exfoliation lasts for 10 minutes, and each mechanical exfoliation is separated by 8 minutes, and finally centrifuge at a speed of 2500 rpm for 30 minutes to remove unexfoliated molybdenum disulfide nanosheets, and take the supernatant through a pipette to obtain a molybdenum disulfide dispersion;

[0039] Step 2: Weigh 400 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water, add 200 mg of graphite fluoride and perform ultrasonic dispersion for 30 minutes, then put it into an autoclave for hydrothermal reaction at 200° C. for 18 hours to obtain an initial fluorinated graphene suspension, and finally centrifuge it at 3500 rpm for 20 minutes to remove the unexfoliated fluorinated graphite ([CFX]n) sheets, and take the supernatant by pipette to obtain a fluorinated graphene dispersion;

[0040] Step 3: Mix the molybdenum disulfide dispersion and the fluorinated graphene dispersion in a mass ratio of 2:1, and perform ultrasonic treatment for 40 minutes to form a molybdenum disulfide / fluorinated graphene composite lubricating additive.

[0041] Example 3: A method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite lubricating additive is as follows:

[0042] Step 1: Weigh 350 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water to form an ionic liquid aqueous solution, add 500 mg of molybdenum disulfide, and then perform ultrasonic dispersion for 28 minutes, and then perform multiple mechanical crushing treatments for a total time of 35 minutes, each mechanical exfoliation lasts for 10 minutes, and each mechanical exfoliation is separated by 10 minutes, and finally centrifuge at a speed of 2600 rpm for 28 minutes to remove unexfoliated molybdenum disulfide nanosheets, and take the supernatant through a pipette to obtain a molybdenum disulfide dispersion;

[0043] Step 2: Weigh 450 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water, add 200 mg of graphite fluoride and perform ultrasonic dispersion for 30 minutes, then put it into an autoclave for hydrothermal reaction at 160° C. for 20 hours to obtain an initial fluorinated graphene suspension, and finally centrifuge it at 3200 rpm for 26 minutes to remove the unexfoliated fluorinated graphite ([CFX]n) sheets, and take the supernatant by pipette to obtain a fluorinated graphene dispersion;

[0044] Step 3: Mix the molybdenum disulfide dispersion and the fluorinated graphene dispersion in a mass ratio of 3:1, and perform ultrasonic treatment for 35 minutes to form a molybdenum disulfide / fluorinated graphene composite lubricating additive.

[0045] After freeze-drying the composite materials prepared in Examples 1-3, the change in the friction coefficient of the lubricating additive of the molybdenum disulfide / fluorinated graphene composite material over time was observed in the friction environments of pure water, oil and artificial seawater, respectively.

[0046] like Figure 4As shown, in a pure water environment, the average friction coefficients of the molybdenum disulfide / fluorinated graphene composite lubricating additives prepared in Examples 1-3 are 0.098, 0.096 and 0.099, respectively. Figure 5 As shown in FIG. 1 , under the PAO No. 4 base oil environment, the average friction coefficients of the molybdenum disulfide / fluorinated graphene composite lubricating additives prepared in Examples 1-3 are 0.0364, 0.0127, and 0.0296, respectively. Figure 6 As shown, in the seawater environment, the average friction coefficients of the molybdenum disulfide / fluorinated graphene composite lubricating additives prepared in Examples 1-3 are 0.1398, 0.0953 and 0.1108, respectively. As the amount of molybdenum disulfide dispersion added increases, the friction coefficient of the prepared molybdenum disulfide / fluorinated graphene composite lubricating additive first decreases and then increases.

[0047] Due to the synergistic effect between molybdenum disulfide and fluorinated graphene, a tribochemical reaction occurs to form a protective film that can reduce friction and wear. The weak van der Waals force and easy shearing between the formed friction films improve the lubrication performance of the friction pair. When the addition ratio of molybdenum disulfide dispersion to fluorinated graphene dispersion is 3:1, the excess molybdenum disulfide nanosheets agglomerate on the friction surface, resulting in a larger friction coefficient. However, compared with the case where no molybdenum disulfide / fluorinated graphene composite lubricant additive is added, the friction coefficient is reduced by 76%, 80% and 63% in the friction environment of pure water, oil and artificial seawater, respectively. This shows that the composite material has excellent lubrication properties and can effectively reduce friction and wear.

[0048] Example 4: A method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite lubricating additive is as follows:

[0049] Step 1: Weigh 300 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water to form an ionic liquid aqueous solution, add 500 mg of molybdenum disulfide, and then perform ultrasonic dispersion for 26 minutes, and then perform multiple mechanical crushing treatments with a total time of 30 minutes. Each mechanical peeling lasts for 10 minutes, and there is an interval of 10 minutes between each mechanical peeling. Finally, centrifuge at a speed of 2800 rpm for 25 minutes to remove the unpeeled molybdenum disulfide nanosheets, and take the supernatant through a pipette to obtain a molybdenum disulfide dispersion;

[0050] Step 2: Weigh 400 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water, add 200 mg of graphite fluoride and perform ultrasonic dispersion for 30 minutes, then put it into an autoclave for hydrothermal reaction at 180° C. for 22 hours to obtain an initial fluorinated graphene suspension, and finally centrifuge it at 3400 rpm for 24 minutes to remove the unexfoliated fluorinated graphite ([CFX]n) sheets, and take the supernatant by pipette to obtain a fluorinated graphene dispersion;

[0051] Step 3: Mix the molybdenum disulfide dispersion and the fluorinated graphene dispersion in a mass ratio of 1.5:1, and perform ultrasonic treatment for 32 minutes to form a molybdenum disulfide / fluorinated graphene composite lubricating additive.

[0052] Example 5: A method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite lubricating additive is as follows:

[0053] Step 1: Weigh 300 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water to form an ionic liquid aqueous solution, add 500 mg of molybdenum disulfide, and then perform ultrasonic dispersion for 30 minutes, and then perform multiple mechanical crushing treatments for a total time of 40 minutes, each mechanical exfoliation lasts for 10 minutes, and each mechanical exfoliation is separated by 5 minutes, and finally centrifuged at a speed of 3000 rpm for 20 minutes to remove the unexfoliated molybdenum disulfide nanosheets, and take the supernatant through a pipette to obtain a molybdenum disulfide dispersion;

[0054] Step 2: Weigh 400 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water, add 200 mg of graphite fluoride and perform ultrasonic dispersion for 30 minutes, then put it into an autoclave for hydrothermal reaction at 170° C. for 24 hours to obtain an initial fluorinated graphene suspension, and finally centrifuge it at 3000 rpm for 25 minutes to remove the unexfoliated fluorinated graphite ([CFX]n) sheets, and take the supernatant by pipette to obtain a fluorinated graphene dispersion;

[0055] Step 3: Mix the molybdenum disulfide dispersion and the fluorinated graphene dispersion in a mass ratio of 2.5:1, and perform ultrasonic treatment for 38 minutes to form a molybdenum disulfide / fluorinated graphene composite lubricating additive.

Claims

1. A method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite lubricating additive, characterized in that: The steps include: Step 1: Weigh 250-350 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water to form an ionic liquid aqueous solution, add 500 mg of molybdenum disulfide, and then perform ultrasonic dispersion, multiple mechanical crushing treatments and centrifugation treatments to obtain the supernatant to obtain a molybdenum disulfide dispersion; Step 2: Weigh 350-450 mg of 1-hexadecyl-3-methylimidazole bromide and add it to 50 mL of deionized water, add 200 mg of graphite fluoride and perform ultrasonic dispersion, then put it into an autoclave for hydrothermal reaction to obtain an initial fluorinated graphene suspension, and take the supernatant after centrifugation to obtain a fluorinated graphene dispersion; Step 3: Mix the molybdenum disulfide dispersion and the fluorinated graphene dispersion in a mass ratio of (1-3):1, and perform ultrasonic treatment to form a molybdenum disulfide / fluorinated graphene composite lubricating additive.

2. The method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite material lubricating additive according to claim 1, characterized in that: The ultrasonic dispersion time in step 1 is 25 to 30 minutes.

3. The method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite material lubricating additive according to claim 1, characterized in that: The total time of the multiple mechanical crushing treatments in step 1 is 30 to 40 minutes, each mechanical peeling lasts for 10 minutes, and the interval between each mechanical peeling is 5 to 10 minutes.

4. The method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite material lubricating additive according to claim 1, characterized in that: The centrifugal treatment in step 1 is performed at a speed of 2500 to 3000 rpm and a centrifugal time of 20 to 30 min.

5. The method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite material lubricating additive according to claim 1, characterized in that: The hydrothermal reaction time in step 2 is 18 to 24 hours, and the hydrothermal reaction temperature is 150 to 200°C.

6. The method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite material lubricating additive according to claim 1, characterized in that: The centrifugal treatment in step 2 is performed at a speed of 3000 to 3500 rpm and a centrifugal time of 20 to 30 min.

7. The method for preparing a highly wear-resistant molybdenum disulfide / fluorinated graphene composite material lubricating additive according to claim 1, characterized in that: The ultrasonic treatment time in step 3 is 30 to 40 minutes.

8. A highly wear-resistant molybdenum disulfide / fluorinated graphene composite lubricating additive prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The structure of the molybdenum disulfide / fluorinated graphene composite material lubricating additive is that molybdenum disulfide nanosheets with a lateral size of 100-300 nm are loaded on fluorinated graphene nanosheets with a lateral size of 1.03 μm.

Citation Information

Patent Citations

  • Molybdenum disulfide / fluorinated graphene-polytetrafluoroethylene composite material as well as preparation method and application thereof

    CN109233177A

  • Method for preparing graphene / molybdenum disulfide / ionic liquid lubricating oil additive through microwave hydrothermal method

    CN116083137A

  • Molybdenum disulfide / modified nitrogen-doped graphene composite material lubricating additive and application

    CN118048199A

  • Preparation method of ionic liquid crystal functionalized nanocellulose water-based lubricant

    CN118184802A

  • LUBRICANT COMPOSITION AND METHOD OF ITS PREPARATION

    RU2014104202A